Indonesia's Concrete Efforts to Ensure Australia's Accountability for Marine Pollution Resulting from the Montara Oil Spill - Latisha, Najwa; Syahda Mauldiyani; Retno Hariarti; Irwan Triadi (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2024)
The marine pollution caused by the Montara oil spill in Australian waters have posed significant challenges to the marine environment, particularly affecting Indonesian waters. This issue remains unresolved as Australia has yet to fulfill its obligations under the provisions of the 1982 United Nations Convention on the Law of the Sea (UNCLOS). This study aims to examine Indonesia's firm and concrete measures to hold Australia accountable for the environmental and economic impacts of the pollution, as well as the appropriate forms of accountability that Australia should undertake in response to Indonesia's claims. This research employs a normative legal methodology, also known as library research, utilizing a legislative approach and an analysis of relevant legal regulations. The results indicate that Indonesia can pursue a combination of diplomatic initiatives, legal actions through international judicial bodies, and expressly acknowledge the economic and political challenges and in compelling Australia's compliance with its obligations. Indonesia should emphasize Australia's accountability by invoking international legal provisions that mandate appropriate compensation for the affected regions and stakeholders. By leveraging an analysis of diplomacy, regional cooperation, and legal approach, this study contributes to a deeper understanding of international legal frameworks and strategies for addressing environmental harm and preserving the sustainability of global marine environment.